Intentional extraction and replantation: The last resort - V T Abdurahiman; Sanju John Jolly; M Abdul Khader (Wolters Kluwer Medknow Publications, 2013)
The importance of the first molar in the development of occlusion is well-known. The difficulties when first molar is not there during the eruption of the second molar and the premolar don't have to be explained much. The construction of a space maintainer in the area of missing first molar is difficult when seven and five are not erupted. The article highlights a case where a grossly decayed first molar with repeated endodontic failures was treated by intentional extraction and replantation as a last resort. A follow-up along with indications and considerations are documented.